Diffuse skin hyperpigmentation associated with chronic minocycline use in a patient with prosthetic joint infection. (2017) - Berbari, Hadi; Berbari, Elie F.; Sia, Irene G.
Abstract: Cutaneous hyperpigmentation is a recognized adverse effect of chronic minocycline use occurring in up to 50% of patients. In this report we present a rare case of extensive skin hyperpigmentation involving both lower extremities in a patient receiving long term minocycline. The patient was receiving minocycline as suppression for chronic prosthetic joint infection. Risk factors associated with minocycline-induced cutaneous pigmentation (MICH) will be reviewed.